2008
DOI: 10.1111/j.1467-3010.2008.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycoprotein and health

Abstract: Mycoprotein is a high protein, high fibre, low fat food ingredient derived from fermentation of the filamentous fungus Fusarium venenatum. Interest in the putative role of mycoprotein in lowering blood cholesterol concentrations, reducing energy intakes and controlling blood sugar levels has generated a small number of human studies investigating the effects of mycoprotein on cholesterol reduction, satiety and insulinaemia/glycaemia.In today's 'obesogenic' environment, in which there is an abundance of foods h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 29 publications
0
76
0
4
Order By: Relevance
“…Mycoprotein in particular, as a meat substitute holds several additional nutritional benefits. These include a shown reduction in blood cholesterol with frequent consumption; improved satiety relative to chicken prepared within comparable test meals; and reduction in glycaemic response (the rate of change in blood glucose) (Turnbull et al, 1993;Denny et al, 2008;Finnigan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mycoprotein in particular, as a meat substitute holds several additional nutritional benefits. These include a shown reduction in blood cholesterol with frequent consumption; improved satiety relative to chicken prepared within comparable test meals; and reduction in glycaemic response (the rate of change in blood glucose) (Turnbull et al, 1993;Denny et al, 2008;Finnigan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The presence and balance of essential fatty acids are an important nutritional consideration for meat and potential replacement products (Wood et al, 2004). Mycoprotein contains both of the essential polyunsaturated fatty acids (linoleic acid of the n-6 series and α-Linolenic acid of the n-3 series); extended randomized control studies have shown essential fatty acid contents of a meat and mycoprotein-substitution diet to be closely balanced (Denny et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations